Feasibility study to examine discrepancy rates in prespecified and reported outcomes in articles submitted to The BMJ. Issue 4 (22nd April 2016) - Weston, Jennifer; Dwan, Kerry; Altman, Douglas; Clarke, Mike; Gamble, Carrol; Schroter, Sara; Williamson, Paula; Kirkham, Jamie
Abstract : Objectives: Adding, omitting or changing prespecified outcomes can result in bias because it increases the potential for unacknowledged or post hoc revisions of the planned analyses. Journals have adopted initiatives such as requiring the prospective registration of trials and the submission of study protocols to promote the transparency of reporting in clinical trials. The main objective of this feasibility study was to document the frequency and types of outcome discrepancy between prespecified outcomes in the protocol and reported outcomes in trials submitted to The BMJ . Methods: A review of all 3156 articles submitted to The BMJ between 1 September 2013 and 30 June 2014. Trial registry entries, protocols and trial reports of randomised controlled trials published by The BMJ and a random sample of those rejected were reviewed. Editorial, peer reviewer comments and author responses were also examined to ascertain any reasons for discrepancies. Results: In the study period, The BMJ received 311 trial manuscripts, 21 of which were subsequently published by the journal. In trials published by The BMJ, 27% (89/333) of the prespecified outcomes in the protocol were not reported in the submitted paper and 11% (31/275) of reported outcomes were not prespecified. In the sample of 21 trials rejected by The BMJ, 19% (63/335) of prespecified outcomes went unreported and 14% (45/317) of reported outcomes were not prespecified. None of the reasons provided by published authors were suggestive of outcome reporting bias as the reasons were unrelated to the results. Conclusions: Mandating the prospective registration of a trial and requesting that a protocol be uploaded when submitting a trial article to a journal has the potential to promote transparency and safeguard the evidence base against outcome reporting biases as a result of outcome discrepancies. Further guidance is needed with regard to documenting reasons for outcome discrepancies.